Thermal performance and applications of Bauhinia Vahlii fiber-reinforced epoxy composites with porcelain Filler: Development and characterization - Thandavamoorthy Raja; Yuvarajan Devarajan; Jayant Ku Nath; Raghavendra Rao P S; Bhumika; Snehal Trivedi; Krishna Kumar Shukla (Case Studies in Thermal Engineering)
This work presents an alternate material for sustainable building, primarily aimed at tile replacement, through the development of a unique Bauhinia Vahlii fiber (BVF)-reinforced epoxy composite infused with porcelain filler. The formulation with 4 % filler (C4) proved to be the most beneficial, demonstrating enhanced mechanical, thermal, and antibacterial qualities, hence serving as a feasible alternative to traditional tile materials. C4 exhibited remarkable mechanical properties, featuring a tensile strength of 42 MPa, compressive strength of 46 MPa, flexural strength of 43 MPa, and an impact strength of 15.92 kJ/m2, hence providing durability for high-stress applications. The Shore D hardness of 53 further validates its appropriateness for rigorous building settings. Thermal investigation demonstrated C4's capacity to endure high temperatures, exhibiting a heat deflection temperature of 98 °C and a thermal conductivity of 1.52 W/mK, underscoring its enhanced thermal stability and suitability for energy-efficient applications. C4, possessing a minimal water absorption rate of 2.4 %, is suitable for moisture-resistant applications in damp environments within structures. Fatigue tests validated its durability, sustaining a fatigue strength of 70 MPa after 10,000 cycles. C4 had notable antibacterial action, producing a 17 mm inhibition zone against Streptococcus pyogenes, comparable to streptomycin's efficacy. Biofilm studies shown significant bacterial suppression, rendering it extremely appropriate for sanitary environments such as kitchens and toilets. The hydrophobic characteristics of C4, evidenced by a contact angle of 89.80°, augment its resistance to moisture and contaminants, so bolstering its viability as a sustainable and high-performance alternative to traditional tiles in contemporary construction.